Impact of Technical Requirements Shifts for Salicylic Acid on Cost Structure and Product Quality in Cosmetic Companies - Hasryani, Waode; Aliza Putriana, Aliza Putriana; Amalia, Eri (Universitas Ahmad Dahlan, 2026)
The strengthening of technical requirements for cosmetic ingredients represents an important regulatory development affecting the cosmetics industry. Salicylic acid, a widely used active ingredient in skincare formulations, is increasingly subject to stricter specifications related to purity, heavy metal contamination, and microbiological quality. This study aims to analyze the impact of enhanced technical requirements for salicylic acid on production costs and product quality in cosmetic manufacturing. The study was conducted using a literature review combined with a regulatory impact analysis based on secondary data from scientific publications, regulatory documents, and comparative market reports related to salicylic acid specifications and pricing. Relevant literature was identified through database searches in Google Scholar, Scopus, and PubMed using keywords such as “salicylic acid,” “cosmetic regulation,” “ingredient specification,” and “cosmetic ingredient safety.” Publications from 2010 to 2024 were considered. Sources were selected based on their relevance to regulatory standards, ingredient quality specifications, and cost implications in cosmetic manufacturing. The analysis indicates that pharmaceutical-grade salicylic acid meeting contemporary specifications may increase raw material costs by approximately 15–35% compared with technical-grade materials. Additional operational costs arise from stricter testing requirements and supplier qualification processes. However, enhanced specifications also contribute to improved product quality, including reduced heavy metal contamination, better microbiological safety, and improved batch consistency. Overall, the regulatory transition creates both compliance challenges and opportunities for the cosmetics industry. While higher standards may increase production costs, improved ingredient quality can enhance product safety and support market differentiation in quality-oriented consumer segments.